Payment Gateway Implementation on Pandansili Tourism, Bareng, Jombang - Lukman Hakim; Galuh Nuril Lathifah; Nanda Zaqia Oktavi (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Pandansili is one of the many tourism villages in Jombang district, located in the village of Ngampungan, Bareng sub-district. In all this time, the payment method is still done manually. To make it easier, so that there are no queues and to reduce direct interactions during the Pandemic, an effective and efficient payment system is needed. From these considerations above, IAIN Kediri took the initiative to design a ticket purchase service system by utilizing a payment gateway, using a marketplace payment method. The development method used in this service is socialization and training which is carried out in a participatory manner with the residents and Pandansili crew. The result of this activity is the QRIS account to facilitate an online payments. Although its use has not been optimal, the crew has recognized its benefits to gradually improve.